Penetapan Kadar Tetrasiklin dalam Air Limbah dengan High Performance Liquid Chromatography-Photodiode Array Detector (HPLC-PDA): Determination of Tetracycline in Wastewater Samples by High Performance Liquid Chromatography-Photodiode Array Detector (HPLC-PDA) - Sanjayadi; Violita, Laurentia Brenda (Universitas Tadulako, 2020)
Tetracycline is an antibiotic that widely used for human treatment and veterinary. Tetracycline is also known as one of the persistent antibiotics in environment. This study aims to develop and validate analysis method for tetracycline in wastewater samples and use this method to determine tetracycline concentration in wastewater samples. The analysis is carried out by extracting samples using SPE C18 and tetracycline was determined by using high-performance liquid chromatography equipped with photodiode array (HPLC-PDA) detector that has been optimized and validated. The result of this study revealed that the developed method was valid enough to determine tetracycline in the range of 0.21 – 3.16 µg/mL showed by the correlation coefficient of 0.999, limit detection and quantification of 0.102 µg/mL and 0.340 µg/mL respectively, precision (RSD) of 5.2 – 5.6% (intra-day) and 4.8 – 5.7% (inter-day) respectively and accuracy (% recovery) of 94.6%. This study shows that tetracycline was not detected in the analyzed wastewater samples.